Gastrointestinal Tracking and Gastric Emptying of Coated Capsules in Rats with or without Sedation Using CT imaging - Noemí Gómez-Lado (Pharmaceutics, 2020)
Following oral administration, gastric emptying is often a rate-limiting step in the absorption of drugs and is dependent on both physiological and pharmaceutical factors. To guide translation into humans, small animal imaging during pre-clinical studies has been increasingly used to localise the gastrointestinal transit of solid dosage forms. In contrast to humans, however, anaesthesia is usually required for effective imaging in animals which may have unintended effects on intestinal physiology. This study evaluated the effect of anaesthesia and capsule size on the gastric emptying rate of coated capsules in rats. Computed tomography (CT) imaging was used to track and locate the capsules through the gastrointestinal tract. Two commercial gelatine mini-capsules (size 9 and 9h) were filled with barium sulphate (contrast agent) and coated using Eudragit L. Under the effect of anaesthesia, none of the capsules emptied from the stomach. In non-anaesthetised rats, most of the size 9 capsules did not empty from the stomach, whereas the majority of the smaller size 9h capsules successfully emptied from the stomach and moved into the intestine. This study demonstrates that even with capsules designed to empty from the stomach in rats, the gastric emptying of such solid oral dosage forms is not guaranteed. In addition, the use of anaesthesia was found to abolish gastric emptying of both capsule sizes. The work herein further highlights the utility of CT imaging for the effective visualisation and location of solid dosage forms in the intestinal tract of rats without the use of anaesthesia.